CONTEMPORARY SOCIETY AS A DIGITAL SOCIETY – THE PHENOMENON OF EXCESSIVE USE OF THE INTERNET AND SMARTPHONES - Aleksandra Dorosz; Igor Gawłowski; Paweł Harbut; Dominika Walczak; Weronika Ewa Nowak; Adrian Kruk; Katarzyna Jakubowska; Aleksandra Miśta; Aleksander Białoń; Lidia Jurczenko (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: The pervasive utilisation of smartphones in contemporary society exerts a substantial influence on individuals’ cognitive, emotional, and social functioning. The objective of this study was to analyse the consequences of intensive use of mobile devices in terms of attention span, working memory, emotional self-regulation and the quality of interpersonal relationships. A review of the extant literature indicates that excessive smartphone use is associated with impaired concentration, increased susceptibility to distraction, shallower learning processes, and an increased tendency towards media multitasking. Furthermore, a correlation has been identified between the compulsive utilisation of electronic devices and elevated levels of stress, anxiety and depressive symptoms, a phenomenon that is partially attributable to dopaminergic reward mechanisms. Within the social sphere, smartphones have been shown to contribute to the fragmentation of communication and a weakening of the sense of closeness. The most efficacious strategies for safeguarding well-being are moderate restrictions on digital stimuli and the cultivation of mindfulness and self-regulation. The results of the study emphasise the need for conscious and sustainable use of technology. The aim of the study: the aim of this article is to examine the impact of intensive smartphone use on cognitive functioning, emotional well-being, and interpersonal relationships. The paper focuses on mechanisms related to attention fragmentation, media multitasking, dopaminergic reward pathways, and the resulting effects on concentration, memory, self-regulation, and the quality of social interactions. Material and Methods of Research: The literature was collected through searches in the PubMed and Google Scholar databases, as well as by reviewing the reference lists of initially selected articles. Keywords included smartphone use, media multitasking, cognitive function, digital well-being, digital detox and mental health. Additionally, statistical data on global smartphone and internet use were obtained from reputable research and analytics platforms, including Paw Research Center, Global Overview Report, Gallup and HarmonyHit. These sources were used to provide up-to-date epidemiological context and quantify the scale of smartphone adoption in the general population. Conclusion: The reviewed evidence indicates that intensive and poorly regulated smartphone use may contribute to diminished attention control, reduced memory efficiency, heightened emotional dysregulation, and a decline in the quality of interpersonal interactions. These effects appear to be mediated by mechanisms of attentional fragmentation and dopaminergic reward sensitivity, which promote habitual and compulsive patterns of device engagement. Developing strategies that support self-regulation, digital awareness, and intentional use of technology is therefore essential for maintaining cognitive balance, emotional well-being, and healthy social functioning in the digital environment.